Analysis of Bird Vocal Bandwidth in Relation to Vegetation Structure Variability in Coffee Agroforestry Systems, Jember, Indonesia - Kurnianto, Agung Sih; Dewi, Nilasari; Haryadi, Nanang Tri; Khowatini, Husnul; Lestari, Ayu; Lestari, Auralia Sakinah; Efendi, Galang Prasetyo; Hanafi, Ahmad Rifqi A.; Kadafi, Ahmad Muammar (Bogor Agricultural University, Indonesia, 2025)
Bird vocalizations are crucial for communication and adaptation to environmental changes. As forests are converted to agriculture, agroforestry plays a key role in conserving biodiversity. This study examines vocal bandwidth variations in four bird species-Common Tailorbird (Orthotomus sutorius), Sooty-headed Bulbul (Pycnonotus aurigaster), Olive-backed Sunbird (Cinnyris jugularis), and Small Minivet (Pericrocotus cinnamomeus)-across three coffee agroforestry sites in Jember, Indonesia: Silo, Kluncing, and Kaliwining. The study explores how vegetation structure influences vocal adaptations using sound recordings, vegetation surveys, the Kruskal-Wallis test, and Pearson correlation analysis. Results show significant vocal bandwidth differences in Common Tailorbird and Sooty-headed Bulbul. Common Tailorbird exhibited the highest bandwidth variation in Silo (2.85 kHz), followed by Kluncing (2.30 kHz) and Kaliwining (1.10 kHz) (p<0.001). Similarly, Sooty-headed Bulbul showed significant variation, with the highest bandwidth in Silo (3.1 kHz), Kaliwining (3.5 kHz), and Kluncing (2.7 kHz) (p<0.001). However, bandwidth variation in Olive-backed Sunbird (p = 0.12) and Small Minivet (p = 0.0014) was not significant. Pearson correlation analysis indicated a strong but non-significant relationship between vegetation structure (Importance Value Index) and Sooty-headed Bulbul presence (R² = 0.8999, p = 0.059). These findings suggest that while vegetation influences some species, other factors like resource availability or human activity may also shape vocal adaptations. This study enhances understanding of bird communication in agroforestry, supporting biodiversity conservation and sustainable land management.